A new population‐based reference curve for symphysis–fundus height. (16th May 2013) - Pay, Aase Serine D.; Frøen, Jan Frederik; Staff, Anne Cathrine; Jacobsson, Bo; Gjessing, Håkon K.
Abstract: Objective: To present a new gestational‐age‐specific percentile curve for symphysis–fundus (SF) height and to determine the effects of maternal and fetal covariates. Design: A population‐based register study. Setting: Antenatal clinics in Västra Götaland County, Sweden, between 2005 and 2010. Population: A total of 42 018 women with ultrasound‐dated singleton pregnancies who delivered at Sahlgrenska University Hospital. Main outcome measures: Measurement of SF height. Methods: A non‐linear regression of SF height on day of pregnancy was used to construct a reference chart for the median and other percentiles of SF height. Results: The new reference curve for SF height showed almost linear growth until term. The median value was considerably larger at each gestational age compared with the curves for SF height used in Norway and Denmark. Compared with the curve currently used in Sweden, higher median values were observed only at gestational ages >34 weeks, accompanied by an upward shift in all percentiles. The only notably influential covariates were maternal pre‐pregnancy weight and height. Conclusions: The new reference curve for SF height shows a pattern that is different from the Scandinavian reference curves of older origin, reflecting changes in the pregnant population, as well as methodological differences. The new curve can be adjusted for maternal and fetal covariates to suit individual pregnancies.